2022
DOI: 10.1002/ccr3.6443
|View full text |Cite
|
Sign up to set email alerts
|

Omphalolith: An underdiagnosed entity

Abstract: The umbilicus is a remaining scar in the center of the abdomen following the removal of the umbilical cord. 1 It has different shapes. Multiple affections can raise in this area including metastasis (Mary Joseph's nodule) and endometriosis. Less commonly reported yet benign conditions are important to diagnose. Omphalolith, also known as omphalokeratolith, omphalith, or umbolith, 2 is a rare and underdiagnosed entity due to the accumulation of sebum and keratin in the umbilicus. Omphalolith is derived from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The authors highlighted the fact that neither a pigment network, dots, globules nor a vascular pattern were present, what supported the differential diagnosis. In another dermoscopic case of omphalolith provided by Jouini et al [ 37 ] the presence of dry crusted pigmented lamellar keratotic material was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors highlighted the fact that neither a pigment network, dots, globules nor a vascular pattern were present, what supported the differential diagnosis. In another dermoscopic case of omphalolith provided by Jouini et al [ 37 ] the presence of dry crusted pigmented lamellar keratotic material was reported.…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Joanna Briggs Institute Appraisal tool questions; Table S2: Risk of bias assessment; Table S3: Overview of the characteristics of included studies. References [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%